2010
DOI: 10.1111/j.1440-1746.2010.06317.x
|View full text |Cite
|
Sign up to set email alerts
|

microRNA expression alteration after arsenic trioxide treatment in HepG‐2 cells

Abstract: Arsenic trioxide altered miRNA expression profile in HepG-2 cells. Among the altered miRNA, miR-29a seemed to take a role in the mechanism of arsenic trioxide in liver cancer therapy. The synergy effect between miR-29a and arsenic trioxide may offer this drug a new chance in cancer therapy by decreasing its dose and toxic side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 31 publications
(54 reference statements)
2
32
0
Order By: Relevance
“…Previous evidence showed that ROS generated by H 2 O 2 (Takagi et al, 2010), hemin (Lal et al, 2009b) or arsenic trioxide (Meng et al, 2011) increased the miR-24 level in human cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…Previous evidence showed that ROS generated by H 2 O 2 (Takagi et al, 2010), hemin (Lal et al, 2009b) or arsenic trioxide (Meng et al, 2011) increased the miR-24 level in human cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…A low level of miR-29 caused loss of inhibition of cyclin E expression, resulting in esophageal carcinoma cell cycle activation (51). Several studies have demonstrated that high expression of miR-29 induces hepatocellular carcinoma cell apoptosis, while downregulation of miR-29 increases HCC tumorigenicity and metastasis (52,53). Mott et al (54) found a high level of miR-29 in normal cholangiocytes by northern blot analysis.…”
Section: Expression Of Mirna-29 In Cancersmentioning
confidence: 98%
“…miR-190 overexpression alone sufficient for acquisition of malignant characteristics in BEAS-2B.Beezold et al, 2011 [77] In vitro exposure to ATO (human hepatocellular carcinoma cell line)4 μM ATO (As 2 O 3 ) for 24 hHuman hepatocellular carcinoma cell line Hep-G2Total RNA analyzed for levels of 677 human miRNAs using a miRNA PCR array. Levels of selected miRNAs analyzed using real-time qPCR.Identified miR-29a as a likely critical mediator of ATO-mediated apoptosis and inhibition of cell growth.Meng et al, 2011 [73] In vitro exposure to arsenite (immortalized human bronchial epithelial cell line)2.5 μM arsenite (NaAsO 2 ) for 16 weeks, resulting in malignant transformationImmortalizedhuman bronchialepithelial cell line p53 low HBEC, which contains stable shRNAknockdown of TP53Total RNA analyzed for levels of 856 human miRNAs using a miRNA PCR array. Levels of selected miRNAs also analyzed using real-time qPCR.Malignant transformation associated with reduction of miR-200 family members; downregulation of miR-200b shown to be essential for malignant transformation.Wang et al, 2011 [76] In vivo exposure to arsenite (chick embryos); in vitro exposure to arsenite (human umbilical cord vein cell line)100 nM arsenite (NaAsO 2 ) injected in yolk sac of chick embryos at HH stages 6, 9, and 12; embryos harvested at HH stage 18.…”
Section: Arsenic and Micrornas (Mirnas)mentioning
confidence: 99%
“…Some of these studies have focused on miRNAs as mediators of the apoptotic effects of arsenic trioxide (ATO) [72, 73], a chemotherapeutic agent used in the treatment of relapsed or refractory acute promyelocytic leukemia [74]. Other studies have indicated miRNAs may play roles in the diverse toxic effects of iAs.…”
Section: Arsenic and Micrornas (Mirnas)mentioning
confidence: 99%